Punch tool based out-of-plane shear behaviour of GFRP composites. (1st March 2017) - Formisano, Antonio; Boccarusso, Luca; Durante, Massimo; Langella, Antonio
Abstract: In this experimental work, the behaviour of unidirectional glass fibre-epoxy composites under a cutting force was studied, in order to better understand the cutting mechanisms of processes involving but not limited to composite materials. Starting from composite panels manufactured by resin infusion process, dedicated specimens were obtained and subjected to a quasi-static punch-shear test. Eight different fibre orientation angles with respect to the direction of the cutting force were considered. For each case, different stress-strain behaviours were observed and discussed. The differences were also investigated, in terms of damage propagation, by means of microscopic observations of the cutting zone.